Problems in The Adoption of Agile-Scrum Software Development Process in Small Organization: A Systematic Literature Review - Putrianasari, Rahmawati; Budiardjo, Eko Kuswardono; Mahatma, Kodrat; Raharjo, Teguh (Sinkron : jurnal dan penelitian teknik informatika, 2024)
Agile methods are becoming increasingly popular in modern corporate strategies, which represents a paradigm change in project management techniques. The concept of pragmatic agility has become essential for enterprises to manage the complexities of ever-changing contexts. However, some organizations—especially small ones with limited resources—face unforeseen difficulties while implementing Agile-Scrum software development. In order to clarify the challenges small businesses, encounter throughout this adoption process, this study combines ideas from fifteen studies into a thorough and systematic analysis of the literature. The issues that have been discovered may be categorized into four primary areas: technology, people, process, and organization, and agile techniques. Organizations are able to anticipate obstacles by using a comprehensive understanding provided by the methodical examination and classification of situations. This proactive approach is essential to preventing unfavorable outcomes, as those seen in the past when implementation errors were made worse by culture problems, insufficient support from upper management, and waning consumer cooperation. This research provides small firms with a navigational aid by synthesizing lessons from the literature, enabling them to plan an Agile-Scrum adoption process that is more smoothly executed. Organizations may enhance their preparation, protect themselves from frequent traps, and ultimately maximize the transformative potential of Agile techniques in their developmental undertakings by adopting these insights.